Host–Multi-Pathogen Warfare: Pathogen Interactions in Co-infected Plants - Abdullah, Araz S.; Moffat, Caroline S.; Lopez-Ruiz, Francisco J.; Gibberd, Mark R.; Hamblin, John; Zerihun, Ayalsew (Frontiers in Plant Science, 2017)
Studies of plant-pathogen interactions have historically focused on simple models of infection involving single host-single disease systems. However, plant infections often involve multiple species and/or genotypes and exhibit complexities not captured in single host-single disease systems. Here, we review recent insights into co-infection systems focusing on the dynamics of host-multi-pathogen interactions and the implications for host susceptibility/resistance. In co-infection systems, pathogen interactions include: (i) Competition, in which competing pathogens develop physical barriers or utilize toxins to exclude competitors from resource-dense niches; (ii) Cooperation, whereby pathogens beneficially interact, by providing mutual biochemical signals essential for pathogenesis, or through functional complementation via the exchange of resources necessary for survival; (iii) Coexistence, whereby pathogens can stably coexist through niche specialization. Furthermore, hosts are also able to, actively or passively, modulate niche competition through defense responses that target at least one pathogen. Typically, however, virulent pathogens subvert host defenses to facilitate infection, and responses elicited by one pathogen may be modified in the presence of another pathogen. Evidence also exists, albeit rare, of pathogens incorporating foreign genes that broaden niche adaptation and improve virulence. Throughout this review, we draw upon examples of co-infection systems from a range of pathogen types and identify outstanding questions for future innovation in disease control strategies.